Characterization of the Colloidal Properties of Dissolved Organic Matter From Forest Soils - Meklesh, Viktoriia; Gentile, Luigi; Andersson, Erika; Bhattacharya, Abhishek; de Farias, Marcelo A.; Cardoso, Mateus B.; Stålbrand, Henrik; Loh, Watson; Škerlep, Martin; Kritzberg, Emma; Tunlid, Anders; Olsson, Ulf; et al. (Frontiers in Soil Science, 2022)
Components of dissolved organic matter (DOM) span from sub-nm molecules to colloidal aggregates of several hundred nm. The colloidal fraction is important for the transport of organic matter and associated elements in the environment, and for the stability of DOM constituents with respect to microbial decomposition. This study focuses on the colloidal properties of DOM extracted from spruce forest soils of a chronosequence. The DOM samples were obtained by common water extraction procedures at 21 oC and 100 oC, respectively. We applied an experimental approach combining chemical analysis with light and X-ray scattering techniques that informed on the colloidal size, charge and structure of DOM. Results showed that two main types of colloids were present: semi-flexible cylinders and fractal aggregates. The cylinders consisted of carbohydrates, presumably hemicelluloses, while the aggregates were a composite material containing a large fraction of carbohydrates together with aliphatics and clay particles. These fractal aggregates dominated the cold-water extracts whereas the strong increase in total organic carbon by hot-water extraction caused a concomitantly strong increase of semi-flexible cylinders, which became the predominant species. Comparison between the chronosequence soils showed that with increasing forest age, the amount of carbon extracted per gram of soil declined and the concentration of the semi-flexible cylinders decreased. Thus, the distribution between the fractal aggregates and cylinders in the forest soil DOM samples depends on the composition of the soil organic matter and the leaching temperature. Changes in this distribution may have important implications for the reactivity and stability of DOM colloids.